2017
DOI: 10.2147/ijnrd.s135899
|View full text |Cite
|
Sign up to set email alerts
|

Sodium–glucose cotransporter-2 inhibition and acidosis in patients with type 2 diabetes: a review of US FDA data and possible conclusions

Abstract: Objective: To evaluate whether adverse event reports to the US Food and Drug Administration on incidents of ketoacidosis from use of sodium glucose cotransport inhibitors (SGLT2 inhibitors) provide insight into ways this new class of drugs is being prescribed with other antihyperglycemic agents; to examine possible mechanisms to explain ketoacidosis. Design and methods: Reports of adverse events concerned to SGLT2 inhibitors, namely, empagliflozin, dapagliflozin, and canagliflozin were obtained under the Freed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…Collectively, the present results suggest that pioglitazone inhibits the increase in ketone production caused by SGLT2i, and we hypothesize that combination therapy with pioglitazone plus SGLT2i will reduce the risk of ketoacidosis in T2DM patients . Consistent with this hypothesis, only four of 64 (6.25%) patients who were receiving pioglitazone as part of their background therapy were reported to have developed ketoacidosis following SGLT2i administration compared to 36% of insulin‐treated T2DM patients . A larger study is warranted to examine whether the addition of pioglitazone to dapagliflozin therapy prevents the SGLT2i‐induced increase in plasma ketone concentration and the development of euglycaemic ketoacidosis reported with SGLT2i therapy .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Collectively, the present results suggest that pioglitazone inhibits the increase in ketone production caused by SGLT2i, and we hypothesize that combination therapy with pioglitazone plus SGLT2i will reduce the risk of ketoacidosis in T2DM patients . Consistent with this hypothesis, only four of 64 (6.25%) patients who were receiving pioglitazone as part of their background therapy were reported to have developed ketoacidosis following SGLT2i administration compared to 36% of insulin‐treated T2DM patients . A larger study is warranted to examine whether the addition of pioglitazone to dapagliflozin therapy prevents the SGLT2i‐induced increase in plasma ketone concentration and the development of euglycaemic ketoacidosis reported with SGLT2i therapy .…”
Section: Discussionsupporting
confidence: 81%
“…In one case series, 59% of T2DM patients who developed diabetic ketoacidosis (n = 34) were receiving two or more daily insulin injections . Moreover, 36% of T2DM patients (n = 640) reported to the adverse event centre of the US Food and Drug Administration as having diabetic ketoacidosis as the result of SGLT2i use were receiving insulin as part of their background therapy, suggesting that the presence of insulin in background antidiabetic therapy does not reduce the risk of diabetic ketoacidosis associated with SGLT2i use. Collectively, the present results suggest that pioglitazone inhibits the increase in ketone production caused by SGLT2i, and we hypothesize that combination therapy with pioglitazone plus SGLT2i will reduce the risk of ketoacidosis in T2DM patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 There have been several reports of diabetic ketoacidosis with the use of SGLT2 inhibitors in both T1D and T2D. 17 In phase II and III studies of SGLT2 inhibitors in patients with T1D the incidence of diabetic ketoacidosis has been as high as 3-9%.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of FDA adverse event reporting data, the authors found 46, 144, and 450 reports of ketoacidosis associated with empagliflozin, dapagliflozin, and canagliflozin. 34 There have been some case reports from southeast Asian countries 35,36 and reports of ketonemia and ketonuria in patients from India.…”
Section: Sodium-glucose Co-transporter-2 Inhibitors In Type 1 Diabetementioning
confidence: 99%